Global Biomaterials Market: Potential Opportunities for Raw Materials of Animal Origin - Marina V. Patshina; Roman A. Voroshilin; Alexey M. Osintsev (Техника и технология пищевых производств)
Introduction. Meat processing enterprises are facing the problem of utilization of secondary products with a limited scope of application and a wide range of useful properties. One of the promising ways of slaughter-house by-product utilization is the production of biomaterials that can replace various tissues of a living organism. This review presents an analysis of the global biomaterials market, its volume, and possible ways of using secondary meat resources in various sectors of economy. Study objects and methods. The article represents some results of a desk research based on open sources, i.e. publications and Internet data portals. Results and discussion. One of the most important tasks of modern regenerative medicine is to develop fast and effective methods for the restoration of damaged or lost organs and tissue fragments. Its solution directly depends on new advanced biomaterials. Modern biocompatible materials are in great demand in such areas of medicine as orthopedics, ophthalmology, dentistry, general and cardiovascular surgery, restorative medicine, drug delivery, etc. Cosmetology is a rapidly evolving segment of medicine and depends on such biomaterials as hyaluronic acid and collagen. Russian biomedicine occupies 0.7% of the world market. However, the Russian segment is likely to grow and expand its range of biomaterials. Conclusion. The currently unused resources of meat industry can be an excellent source of valuable raw materials for the advanced biomedical structures used in tissue engineering. A wide variety of structures and properties of secondary resources can produce a wide range of biomaterials. The possibility of manufacturing matrices from internally sourced raw materials within one enterprise is particularly promising.